2018
DOI: 10.1108/md-04-2017-0296
|View full text |Cite
|
Sign up to set email alerts
|

Empowering women and stimulating development at bottom of pyramid through micro-entrepreneurship

Abstract: Purpose The purpose of the paper is to address the sustainability issue of Self-help groups by means of developing small business/micro-entrepreneurs. Design/methodology/approach The causal relationship between empowerment through SHG and micro-entrepreneurship is being investigated by estimating empirical data through structural equation modelling with second-order latent factor. Findings Empirical examination supports the causal relationship between empowerment through SHG and small business. Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 31 publications
3
61
0
Order By: Relevance
“…Overall, the current study makes two contributionsone, advancing literature on financial inclusion of women in urban slums and two, assessing the impact of recently launched financial inclusion schemes by the Government of India. As recognized in this study, all sorts of financial inclusion processes have the ability to impact the empowerment of women and this is in line with the available literature which suggests that financial inclusion has an impact on the social empowerment of women (Al-Mamun et al, 2014;Basu, 2006;Blattman, Green, Annan, & Jamison, 2013;Chatterjee et al, 2018;Goetz & Gupta, 1996;Rahaman, 1999;Weber & Ahmad, 2014;Wrigley-Asante, 2012). Similarly, the results of financial inclusion and political empowerment (Basu, 2006;Bhattacharyya, 2019;Hashemi, Schuler, & Riley, 1996;Kabeer, 1999;Malhotra & Schuler, 2005) and economic empowerment (Datta & Sahu, 2017;Bayulgen, 2015;Hashemi et al, 1996;Kabeer, 1999) are consistent with the literature.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Overall, the current study makes two contributionsone, advancing literature on financial inclusion of women in urban slums and two, assessing the impact of recently launched financial inclusion schemes by the Government of India. As recognized in this study, all sorts of financial inclusion processes have the ability to impact the empowerment of women and this is in line with the available literature which suggests that financial inclusion has an impact on the social empowerment of women (Al-Mamun et al, 2014;Basu, 2006;Blattman, Green, Annan, & Jamison, 2013;Chatterjee et al, 2018;Goetz & Gupta, 1996;Rahaman, 1999;Weber & Ahmad, 2014;Wrigley-Asante, 2012). Similarly, the results of financial inclusion and political empowerment (Basu, 2006;Bhattacharyya, 2019;Hashemi, Schuler, & Riley, 1996;Kabeer, 1999;Malhotra & Schuler, 2005) and economic empowerment (Datta & Sahu, 2017;Bayulgen, 2015;Hashemi et al, 1996;Kabeer, 1999) are consistent with the literature.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, political factors such as political quotas, awareness, and voting rights are important interventions in this regard (Armendáriz & Morduch, 2010;Deininger & Liu, 2013;Kabeer, 1999;Sundström, Paxton, Wang, & Lindberg, 2017). Administrative framework, social standards, independence in basic leadership, social versatility and systems additionally significantly affect women empowerment procedures (Bandiera et al, 2018;Beteta, 2006;Chatterjee, Gupta, & Upadhyay, 2018;Kumar et. al., 2019).…”
Section: Political Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Quayes (2012) results suggest a positive impact of microfinance on economic development while other studies argue that only loans for productive purposes have a positive effect on economic development (Imai et al 2010;Vial and Hanoteau 2015). Chatterjee et al (2018) found that group based financial services to micro-enterprises empower women borrowers and translate into economic up-liftment. On the other hand, Morduch (1998) argues that micro-credit has only minimal impact on poverty reduction because it rather supports borrowers to create basic incomes instead of driving fundamental economic shifts.…”
Section: Conceptual Frameworkmentioning
confidence: 95%
“…Craftsman behavior is characterized by precise routines beyond mere production activities; it includes the choice of raw materials and techniques, processing procedure, and packaging. Numerous studies report that craftsmen are not stimulated by financial and growth motives, but have personal satisfaction and lifestyle goals (Hornaday, 1990;Fillis, 2002;Greenhalgh, 2003;Poettschacher, 2005;Chatterjee et al, 2017). Everything is done with a focus on the consumer.…”
Section: Craft and The Rediscovery Of Craftworkmentioning
confidence: 99%